Corrosion behaviour of aluminide coatings on Ti-based alloy in the marine environment at high temperature. (December 2022) - Zhang, Mingming; Liang, Yu; Feng, Min; Jiang, Chengyang; Zhang, Yaqi; Wang, Yahui; Feng, Yipeng; Ma, Lijie; Wang, Fuhui
Abstract: Ni-Al aluminide coating was deposited by electroplating of Ni and subsequent aluminisation while Ti-Al aluminide coating was deposited by aluminisation directly on Ti-based alloy. The corrosion performance of two coated samples with uncoated sample in marine environment in the presence of NaCl and water vapour at 700 °C were studied. Ni-Al coated sample showed the best corrosion resistance. Ti-Al coated sample showed severer corrosion in marine environment compared with that in static air due to self-sustainable oxychlorination process. The detrimental effect of Ti and beneficial effect of Ni-plating on self-sustainable oxychlorination in marine environment are discussed. Highlights: The corrosion behaviour of Ti-Al coating was facilitated under the synergetic effect of NaCl and H2 O(g) . The corrosion product Na2 TiO3 was detected in Ti-Al coating during self-sustainable oxychlorination process. The self-sustainable oxychlorination process in Ni-Al coating was greatly inhibited by pre-eletroplating Ni layer.